Multi-objective Optimization of Bandwidth Broker with Evolutionary Algorithm - Lauks, G. (Elektronika ir Elektrotechnika, 2005)
The Optical Transport Networks with dynamic transport routing capability enable rearrangement of the logical link capacities on demand in real time. In this paper an evolutionary algorithm based approach for multi-objective optimization of Bandwidth Broker (BB) is presented. BB is represented as evolutionary process in dynamically changed traffic demand environment. Multi-objective Evolutionary algorithm scheme for bandwidth allocation is described. The suitability of Evolutionary algorithm approach is investigated. The Pareto optimal solutions are ensured by the underlying genetic operators. There are carried out a few experiments and the test results illustrate the trade-off between objectives and ability of this approach to produce many good compromise solutions. Ill.3, bibl.8 (in English; summaries in Lithuanian, English and Russian).